Silicon negative electrode material as well as negative electrode plate and lithium battery applying same

By covering the silicon material and introducing specific monomers, the problem of degradation in the cycle performance of silicon material due to volume expansion during charging and discharging of lithium batteries is solved, and the overall performance of lithium batteries is improved by improving conductivity and structural stability.

CN119725450APending Publication Date: 2025-03-28EVE ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411901409.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Silicon materials have deteriorated cycling performance due to volume expansion during charging and discharging of lithium batteries, and poor conductivity limits their commercial application.

Method used

The silicon material is coated with a polymer containing a specific monomer, forming a coating layer to buffer volume expansion, and improving conductivity and structural stability through thiophen groups and heteroboranes.

Benefits of technology

It effectively reduces the risk of SEI film rupture caused by volume expansion of silicon negative electrode materials during charging and discharging of lithium batteries, improves the circulation and rate performance of lithium batteries, and enhances structural and chemical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725450A_ABST
    Figure CN119725450A_ABST
Patent Text Reader

Abstract

The invention provides a silicon negative electrode material as well as a negative electrode plate and a lithium battery applying the silicon negative electrode material. The silicon negative electrode material comprises a silicon material and a coating layer coating the surface of the silicon material, the coating layer contains a polymer, and the polymer comprises a monomer as shown in a formula I; x is selected from one of-H, alkyl and cyano; and Y is a heterocyclic ring containing a B atom. The coating layer of the silicon negative electrode material can well buffer volume expansion of the silicon material during charging and discharging, the risk that an SEI film on the surface of a negative electrode plate is broken due to the volume expansion of the silicon negative electrode material during charging and discharging of a lithium battery is reduced, and the polymer structure of the coating layer contains a large pi bond, so that the silicon negative electrode material is endowed with good conductivity, and the service life of the silicon negative electrode material is prolonged. The problem of poor electrical conductivity of the silicon material is improved, the impurity borane contained in the silicon material can absorb HF generated in an electrolyte, the erosion effect of HF on a silicon negative electrode or a silicon positive electrode can be avoided, and the cycle performance and the rate capability of the lithium battery applying the silicon negative electrode material are improved through the effect. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a silicon negative electrode material and a negative electrode sheet and a lithium battery using the same. Background Art

[0002] Lithium batteries are widely used in consumer electronics, automobiles and other fields due to their advantages such as high operating voltage, high energy density and long cycle life.

[0003] Negative electrode materials for lithium batteries are mainly divided into carbon-based materials and non-carbon-based materials. Among them, carbon-based materials are mainly common graphite, while non-carbon-based materials are mainly silicon materials. Compared with graphite, silicon materials have a higher energy density (4200mAh / g), making it a research hotspot for negative electrode materials. However, silicon materials are prone to volume expansion during the charging and discharging process, with an expansion rate of up to 300%. The huge volume expansion can easily cause the silicon particles to break and pulverize, thereby affecting the cycle performance of lithium batteries using silicon materials as negative electrode materials. In addition, the conductivity of silicon materials is poor, which will greatly limit the commercial application of silicon materials as negative electrode materials for lithium batteries. Summary of the invention

[0004] In order to solve the problem that the cycle performance of lithium batteries using existing silicon materials decreases due to huge volume expansion during the charge and discharge process, the present invention provides a silicon negative electrode material and a negative electrode sheet and a lithium battery using the same.

[0005] According to a first aspect of the present invention, there is provided a silicon negative electrode material, the silicon negative electrode material comprising a silicon material and a coating layer coated on the surface of the silicon material, the coating layer comprising a polymer, the polymer comprising a monomer as shown in formula I;

[0006]

[0007] X is selected from -H, alkyl, cyano;

[0008] Y is a heterocyclic ring containing a B atom.

[0009] In the silicon negative electrode material provided by the present invention, the polymer formed by the polymerization reaction of the monomer as shown in Formula I is used to coat the silicon material, and the silicon negative electrode material is applied to the negative electrode sheet and the lithium battery. First, the polymer formed by the polymerization reaction of the monomer as shown in Formula I can effectively buffer the volume expansion of the silicon material during the charging and discharging process, thereby reducing the risk of rupture of the SEI film formed on the surface of the negative electrode sheet due to the volume expansion of the silicon negative electrode material during the charging and discharging process of the lithium battery, thereby improving the cycle performance of the negative electrode sheet and the lithium battery. Second, the monomer as shown in Formula I contains a thiophene group, so that the polymer structure used to form the coating layer The large π bond in the coating layer gives the coating layer good conductivity, improves the problem of poor conductivity of the silicon material, and thus improves the rate performance of the lithium battery using the silicon negative electrode material provided by the present invention. Thirdly, the monomer shown in Formula I contains heteroborane, and the polymer obtained by polymerization reaction is used as the coating layer material of the silicon material. The heteroborane contained in the coating layer can absorb HF generated in the electrolyte, which is beneficial to avoid the corrosion of HF on the silicon negative electrode or positive electrode, thereby improving the structural stability and chemical stability of the silicon negative electrode material, giving the lithium battery using the silicon negative electrode material good cycle performance, so that the lithium battery can still maintain a high capacity retention rate after multiple cycles.

[0010] Preferably, Y is R1, R2, R3, and R4 are independently selected from -H and alkyl.

[0011] Preferably, the polymer comprises a monomer as shown in formula II;

[0012]

[0013] The silicon negative electrode material involved in this scheme uses a polymer formed by polymerization reaction of a monomer as shown in Formula II to coat the silicon material, so that the rate performance and cycle performance of the lithium battery using the silicon negative electrode material are further improved.

[0014] Preferably, the number average molecular weight of the polymer is 3,000 to 20,000.

[0015] The number average molecular weight of the polymer used to form the coating layer is controlled within the above range. First, the bonding strength of the coating layer can be moderate, which is beneficial to reduce the risk of the coating layer falling off or peeling off during the actual application of the silicon negative electrode material. Second, the coating layer has good mechanical strength, which can improve the buffering effect of the coating layer on the volume expansion of silicon during the charging and discharging process of the silicon negative electrode material. Third, the coating layer has good uniformity and density, which can improve the cycle stability of the silicon negative electrode material during multiple charging and discharging processes.

[0016] If the number average molecular weight of the polymer used to form the coating layer is too small, the bonding strength of the coating layer will be low, the coating layer will easily fall off or peel off during the charge and discharge cycle, and the mechanical strength of the polymer will be low; if the number average molecular weight of the polymer used to form the coating layer is too large, the solubility of the polymer in organic solvents will deteriorate, which will increase the difficulty of coating and affect the uniformity and density of the coating layer.

[0017] Preferably, the coating layer accounts for 2-6% by mass in the silicon negative electrode material.

[0018] Preferably, the coating layer has a thickness of 10 to 110 nm.

[0019] Controlling the mass percentage and thickness of the coating layer within the above range can further improve the lithium ion transmission performance, rate performance and cycle performance of the silicon negative electrode material, and give the coating layer good flexibility.

[0020] If the mass proportion of the coating layer is too small and the thickness is too thin, the coating layer will easily break during multiple cycles of charge and discharge, resulting in loss of active lithium; if the mass proportion of the coating layer is too large and the thickness is too thick, the ion transport performance of the silicon negative electrode material will be poor, resulting in a decrease in its rate performance and cycle performance.

[0021] Preferably, the particle size D50 of the silicon negative electrode material is 3-7 μm.

[0022] Preferably, the specific surface area of ​​the silicon negative electrode material is 1 to 8 m 2 / g.

[0023] Controlling the specific surface area of ​​the silicon negative electrode material within the above range can improve the stability of the silicon negative electrode material and enable its capacity to be better utilized during the cyclic charge and discharge process.

[0024] If the specific surface area of ​​the silicon negative electrode material is too small, its contact area with the electrolyte is too small, which may cause the internal resistance of the lithium battery using the silicon negative electrode material to be relatively high, limiting the performance of the silicon negative electrode material; if the specific surface area of ​​the silicon negative electrode material is too large, the silicon negative electrode material is more likely to agglomerate during the preparation of the negative electrode sheet, making the dispersion of the material more difficult, thereby affecting the performance of the negative electrode sheet.

[0025] Preferably, the silicon negative electrode material is prepared by the following steps:

[0026] S1. preparing a polymer solution by using a polymer and an organic solvent;

[0027] S2. Applying the polymer solution to the surface of the silicon material, and drying the polymer solution on the surface of the silicon material to form a coating layer on the surface of the silicon material.

[0028] Preferably, in S1, the mass fraction of the polymer solution is 3-18%.

[0029] Preferably, in S1, the polymer is prepared by the following steps: mixing the monomer for preparing the polymer with an organic solvent and an initiator and reacting the mixture under an inert protective gas at 50 to 100° C. for 3 to 12 hours to obtain the polymer.

[0030] Preferably, S1 includes the following operations: mixing the monomer for preparing the polymer with an organic solvent and an initiator and reacting them under an inert protective gas at 50-100° C. for 3-12 hours to obtain a reaction solution, adding the reaction solution to a precipitation solvent to obtain a polymer precipitate, washing and drying to obtain a polymer, and dissolving the polymer in an organic solvent to prepare a polymer solution.

[0031] Preferably, the organic solvent includes at least one of benzene, toluene, N-methylpyrrolidone (NMP), tetrahydrofuran (THF), and N,N-dimethylformamide (DMF).

[0032] Preferably, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, and dibenzoyl peroxide (BPO).

[0033] Preferably, the precipitation solvent includes at least one of propanol, isopropanol and acetone.

[0034] Preferably, in S1, the amount of the initiator used is 0.1 to 0.8% of the total mass of the monomers used to prepare the polymer.

[0035] Preferably, S2 includes the following operations: mixing the silicon material and the polymer solution and stirring at 30-80° C. for 4-10 hours to obtain a mixed solution, and spray-drying the mixed solution to obtain a silicon negative electrode material.

[0036] Preferably, in S2, the inlet temperature of the spray drying is 100-200°C, and the outlet temperature is 60-90°C.

[0037] Preferably, the silicon material includes at least one of silicon monoxide (SiO) and silicon carbon material (SiC).

[0038] Preferably, the silicon-carbon material includes a porous carbon skeleton, a silicon layer and a carbon layer, the porous carbon skeleton includes an inner layer region and an outer layer region wrapping the inner layer region, the inner layer region has a plurality of inner holes, the outer layer region has a plurality of outer holes, the silicon layer is arranged on the inner walls of the inner holes and the outer holes, and the carbon layer is arranged on the surface of the silicon layer in the outer holes, so that the silicon-carbon particles have inner pores in the inner layer region and outer pores in the outer layer region.

[0039] Preferably, among the internal pores and external pores of the silicon-carbon material, the proportion of mesopores is 42-86%, and the proportion of micropores is less than 58%, wherein the diameter of the mesopores is 3-40 nm, and the diameter of the micropores is 0.5-2 nm.

[0040] According to a second aspect of the present invention, a negative electrode sheet is provided. The negative electrode sheet includes a negative electrode current collector and a negative electrode active coating disposed on the surface of the negative electrode current collector, wherein the negative electrode active coating contains the above-mentioned silicon negative electrode material.

[0041] According to a third aspect of the present invention, a lithium battery is provided, the lithium battery comprising the above-mentioned negative electrode sheet.

[0042] Applying the silicon negative electrode material provided by the present invention to negative electrode sheets and lithium batteries is beneficial to improving the rate performance and cycle performance of lithium batteries. DETAILED DESCRIPTION

[0043] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] A lithium battery is prepared by the following steps:

[0046] 1. Preparation of negative electrode

[0047] Silicon negative electrode material, conductive carbon black (SP), single-walled carbon nanotube (SWCNT), and binder polyacrylic acid (PAA) were mixed in a mass ratio of 80:9:1:10 and added to deionized water as a solvent, and mixed evenly to prepare a negative electrode slurry with a solid content of 30%. The negative electrode slurry was coated on both surfaces of the negative electrode current collector copper foil to form a negative electrode active coating, and after vacuum drying and cold pressing, a negative electrode sheet was prepared;

[0048] The silicon negative electrode material comprises a silicon material and a coating layer coated on the surface of the silicon material, wherein the coating layer contains a polymer, and the polymer comprises a monomer as shown in Formula II;

[0049]

[0050] The above silicon negative electrode material is prepared by the following steps:

[0051] S1. The monomer shown in formula II is mixed with an organic solvent DMF and an initiator BPO, and reacted under argon protection at 75° C. for 8 hours to obtain a reaction solution, and the reaction solution is added to acetone to obtain a polymer precipitate, and after washing and drying, a polymer having a number average molecular weight between 10,000 and 12,000 is obtained, and the polymer is dissolved in DMF to prepare a polymer solution having a mass fraction of 10%;

[0052] S2. Add the silicon material to the polymer solution and stir at 60°C for 7h to obtain a mixed solution, spray dry the mixed solution to form a coating layer with a thickness of 70nm on the surface of the silicon material, and obtain a silicon negative electrode material with a particle size D50 of 5μm, wherein the coating layer accounts for 4% by mass in the silicon negative electrode material, the inlet temperature of the spray drying is 150°C, and the outlet temperature is 75°C;

[0053] The silicon material involved in this embodiment is silicon-carbon material.

[0054] 2. Preparation of positive electrode

[0055] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive carbon black (SP) and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:2 and added to a solvent N-methylpyrrolidone (NMP). The mixture is evenly mixed to obtain a positive electrode slurry with a solid content of 45%. The positive electrode slurry is coated on both surfaces of the positive electrode current collector aluminum foil to form a positive electrode active coating. After vacuum drying and cold pressing, a positive electrode sheet is obtained.

[0056] 3. Preparation of Diaphragm

[0057] A polyethylene (PE) film containing a ceramic layer is used as the diaphragm.

[0058] 4. Preparation of Electrolyte

[0059] Ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC) are mixed in a mass ratio of 20:40:30:10 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1M.

[0060] 5. Assembly of lithium batteries

[0061] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell, which is placed in an outer packaging shell, dried and injected with the above-mentioned electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium battery.

[0062] Example 2

[0063] This embodiment provides a lithium battery. Compared with the embodiment 1, the difference in structure is that the preparation method of the silicon negative electrode material used in the negative electrode sheet is different.

[0064] The silicon negative electrode material used in this embodiment is prepared by the following steps:

[0065] S1. The monomer shown in formula II is mixed with an organic solvent DMF and an initiator BPO, and reacted under argon protection at 50° C. for 12 hours to obtain a reaction solution, and the reaction solution is added to acetone to obtain a polymer precipitate, and after washing and drying, a polymer having a number average molecular weight between 3000 and 4000 is obtained, and the polymer is dissolved in DMF to prepare a polymer solution having a mass fraction of 3%;

[0066] S2. Add the silicon material to the polymer solution and stir for 10 hours at 30°C to obtain a mixed solution, spray dry the mixed solution to form a coating layer with a thickness of 10 nm on the surface of the silicon material, and obtain a silicon negative electrode material with a particle size D50 of 3 μm, wherein the coating layer accounts for 2% by mass in the silicon negative electrode material, the inlet temperature of the spray drying is 100°C, and the outlet temperature is 60°C;

[0067] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0068] Example 3

[0069] This embodiment provides a lithium battery. Compared with the embodiment 1, the difference in structure is that the preparation method of the silicon negative electrode material used in the negative electrode sheet is different.

[0070] The silicon negative electrode material used in this embodiment is prepared by the following steps:

[0071] S1. The monomer shown in formula II is mixed with an organic solvent DMF and an initiator BPO, and reacted under argon protection at 100° C. for 3 hours to obtain a reaction solution, and the reaction solution is added to acetone to obtain a polymer precipitate, and after washing and drying, a polymer having a number average molecular weight between 18,000 and 20,000 is obtained, and the polymer is dissolved in DMF to prepare a polymer solution having a mass fraction of 6%;

[0072] S2. Add the silicon material to the polymer solution and stir at 80°C for 4h to obtain a mixed solution, spray dry the mixed solution to form a coating layer with a thickness of 110nm on the surface of the silicon material, and obtain a silicon negative electrode material with a particle size D50 of 7μm, wherein the mass proportion of the coating layer in the silicon negative electrode material is 6%, the inlet temperature of the spray drying is 200°C, and the outlet temperature is 90°C;

[0073] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0074] Example 4

[0075] This embodiment provides a lithium battery, which is different from that of the embodiment 1 in that the coating layer in the silicon negative electrode material contains a different polymer, and the monomer used is shown in Formula III;

[0076]

[0077] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0078] Example 5

[0079] This embodiment provides a lithium battery, which is different from that of the embodiment 1 in that the coating layer in the silicon negative electrode material contains a different polymer, and the monomer used is shown in Formula IV;

[0080]

[0081] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0082] Example 6

[0083] This embodiment provides a lithium battery. Compared with the embodiment 1, the difference in structure is that in the preparation step S1 of the silicon negative electrode material, the monomer is mixed with the organic solvent DMF and the initiator BPO and reacted at 48°C under argon protection for 8 hours, and the number average molecular weight of the obtained polymer is 1500-2500.

[0084] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0085] Example 7

[0086] This embodiment provides a lithium battery. Compared with the embodiment 1, the difference in structure is that in the preparation step S1 of the silicon negative electrode material, the monomer is mixed with the organic solvent DMF and the initiator BPO and reacted under argon protection at 105°C for 8 hours, and the number average molecular weight of the obtained polymer is 23000-25000.

[0087] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0088] Example 8

[0089] This embodiment provides a lithium battery, which has the following differences in structure compared with Embodiment 1: (1) in the step S1 of preparing the silicon negative electrode material, the mass fraction of the polymer solution is 1%; (2) in the step S2 of preparing the silicon negative electrode material, the particle size D50 of the silicon negative electrode material finally obtained is 2 μm, the thickness of the formed coating layer is 7 nm, and the mass fraction of the coating layer in the silicon negative electrode material is 0.5%.

[0090] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0091] Example 9

[0092] This embodiment provides a lithium battery, and compared with Embodiment 1, the differences in structure are: (1) in the preparation step S1 of the silicon negative electrode material, the mass fraction of the polymer solution is 20%; (2) in the preparation step S2 of the silicon negative electrode material, the particle size D50 of the silicon negative electrode material finally obtained is 10 μm, the thickness of the formed coating layer is 130 nm, and the mass fraction of the coating layer in the silicon negative electrode material is 10%.

[0093] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0094] Comparative Example 1

[0095] This comparative example provides a lithium battery. Compared with Example 1, the difference in structure is that the silicon negative electrode material used in the preparation process of the negative electrode sheet is a silicon material without a coating layer.

[0096] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0097] Comparative Example 2

[0098] This comparative example provides a lithium battery, which is different from Example 1 in structure in that the coating layer in the silicon negative electrode material contains a different polymer, and the monomer used is shown in Formula V;

[0099]

[0100] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0101] Comparative Example 3

[0102] This comparative example provides a lithium battery, which is different from Example 1 in structure in that the coating layer in the silicon negative electrode material contains a different polymer, and the monomer used is shown in Formula VI;

[0103]

[0104] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0105] Comparative Example 4

[0106] This comparative example provides a lithium battery, which is different from Example 1 in structure in that the coating layer in the silicon negative electrode material contains a different polymer, and the monomer used is shown in Formula VII;

[0107]

[0108] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0109] Comparative Example 5

[0110] This comparative example provides a lithium battery, which is different from Example 1 in structure in that the coating layer in the silicon negative electrode material contains a different polymer, and the monomer used is shown in Formula VIII;

[0111]

[0112] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0113] Test Case

[0114] 1. Participants

[0115] In this test example, the lithium batteries prepared in Examples 1 to 9 and Comparative Examples 1 to 5 were used as test objects to conduct relevant performance tests.

[0116] 2. Test content

[0117] (1) First Coulomb efficiency

[0118] At 25°C, the lithium battery was charged to 4.2V at a constant current and constant voltage rate of 0.33C and allowed to stand for 10 minutes. Then, the lithium battery was discharged to 2.5V at a constant current rate of 0.33C and allowed to stand for 10 minutes. The first coulombic efficiency of the lithium battery was calculated.

[0119] First coulombic efficiency (%) = total capacity of lithium battery discharged at 0.33C for the first time / total capacity of lithium battery charged at 0.33C for the first time × 100%.

[0120] (2) Capacity retention rate after 1200 cycles at 1C / 1C at room temperature

[0121] At 25°C, the lithium battery is charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the lithium battery is discharged to 2.5V at a constant current rate of 1C and allowed to stand for 10 minutes. This is considered one charge and discharge cycle. The lithium battery is charged and discharged for 1200 cycles according to the above method, and the capacity retention rate after 1200 cycles of charge and discharge at 1C / 1C is calculated.

[0122] The capacity retention rate (%) of a lithium battery after N cycles = (discharge capacity at the Nth cycle / first discharge capacity) × 100%, where N is the number of cycles of the lithium battery.

[0123] (3) Room temperature 6C rate performance - constant current charging ratio

[0124] At 25°C, the lithium battery was discharged at a constant current rate of 1C to 2.5V and allowed to stand for 10 minutes. Then, the lithium battery was charged at a constant current and constant voltage rate of 6C to 4.2V, with a cut-off current of 0.05C and allowed to stand for 10 minutes. The 6C constant current charging capacity Q1, the 6C constant current and constant voltage charging total capacity Q2 and the highest temperature during the fast charging process (i.e., the highest temperature of 6C rate charging) of the lithium battery were recorded. The 6C rate charging constant current charging ratio was calculated according to the following formula: 6C rate charging constant current charging ratio = 6C constant current charging capacity Q1 / 6C constant current and constant voltage charging total capacity Q2 × 100%, wherein, the constant current and constant voltage charging total capacity Q2 = constant current charging capacity + constant voltage charging capacity.

[0125] (4) 1C / 10C discharge capacity retention rate at room temperature

[0126] At 25°C, the divided lithium battery is charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C. After standing for 10 minutes, the lithium battery is discharged to 2.5V at a constant current rate of 1C, and its discharge capacity Q is recorded. 1C As the initial discharge capacity; then at 25 ° C, the lithium battery is charged to 4.2V at a constant current and constant voltage rate of 1C, the cut-off current is 0.05C, and it is left to stand for 10 minutes. Then, the fully charged lithium battery is discharged to 2.5V at a constant current rate of 10C, and its discharge capacity Q is recorded. 10C ; Calculate the discharge capacity retention rate of the lithium battery at 1C / 10C rate according to the following formula: Discharge capacity retention rate (%) = discharge capacity Q at 10C rate 10C / Discharge capacity at 1C rate Q 1C ×100%.

[0127] 3. Experimental results

[0128] Table 1. Test results of relevant performance of lithium battery

[0129]

[0130] The relevant performance test results of the lithium batteries prepared in Examples 1 to 9 and Comparative Examples 1 to 5 are shown in Table 1.

[0131] The silicon negative electrode material used in the lithium battery provided in Comparative Example 1 is a silicon material without a coating layer, while the silicon negative electrode material used in the lithium batteries provided in Examples 1 to 9 is obtained by coating the silicon material with a polymer formed by a polymerization reaction of the monomer shown in Formula I. The test results show that the first coulomb efficiency, the capacity retention rate of 1200 cycles at room temperature 1C / 1C, the constant current charging ratio of 6C rate charging, and the discharge capacity retention rate of 1C / 10C at room temperature of the lithium batteries provided in Examples 1 to 9 are significantly higher than those in Comparative Example 1. The above results indicate that coating the silicon material with a polymer formed by a polymerization reaction of the monomer shown in Formula I can play a good buffering role in the volume expansion of the silicon material during the charging and discharging process, thereby reducing the silicon negative electrode material in The risk of rupture of the SEI film formed on the surface of the negative electrode sheet due to volume expansion during the charge and discharge process of the lithium battery is reduced, and the cycle performance of the lithium battery is improved. The monomer shown in Formula I contains a thiophene group, so that the polymer structure used to form the coating layer contains a large π bond, which gives the coating layer good conductivity and improves the problem of poor conductivity of the silicon material, thereby improving the rate performance of the lithium battery using the silicon negative electrode material. In addition, the heteroborane contained in the coating layer can absorb HF generated in the electrolyte, which is beneficial to avoid the corrosion of HF on the silicon negative electrode or positive electrode, thereby improving the structural stability and chemical stability of the silicon negative electrode material, giving the lithium battery using the silicon negative electrode material good cycle performance, so that the lithium battery can still maintain a high capacity retention rate after multiple cycles.

[0132] By comparing the test results of Examples 1, 4, 5 and Comparative Examples 2, 3, 4, 5, it can be shown that, compared with monomers of other structures, the silicon negative electrode material obtained by coating the silicon-based material with a polymer formed by the polymerization reaction of the monomer shown in Formula II in Example 1 has better cycle performance and rate performance. In addition, in the lithium battery provided in Example 5, the monomer contained in the polymer used to form the coating layer contains a cyano group, which is easily oxidized and unstable when the ternary positive electrode releases oxygen, thereby causing the cycle performance and rate performance of the lithium battery in Example 5 to be worse than that in Example 1.

[0133] By comparing the test results of Examples 1, 6 and 7, it can be shown that the silicon negative electrode material obtained by coating the silicon material with a polymer having a number average molecular weight in the range of 3000 to 20000 has better cycle performance and rate performance.

[0134] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A silicon negative electrode material, characterized in that: The silicon negative electrode material comprises a silicon material and a coating layer coated on the surface of the silicon material, wherein the coating layer contains a polymer, and the polymer comprises a monomer as shown in Formula I; The X is selected from one of —H, alkyl, and cyano; The Y is a heterocyclic ring containing a B atom.

2. The silicon negative electrode material according to claim 1, characterized in that: The Y is The R1, R2, R3 and R4 are independently selected from -H and alkyl.

3. The silicon negative electrode material according to claim 2, characterized in that: The polymer includes a monomer as shown in formula II; 4. The silicon negative electrode material according to claim 1, characterized in that: The number average molecular weight of the polymer is 3,000 to 20,000.

5. The silicon negative electrode material according to claim 1, characterized in that: The coating layer accounts for 2-6% of the silicon negative electrode material by mass, and / or the coating layer has a thickness of 10-110 nm.

6. The silicon negative electrode material according to claim 1, characterized in that: The particle size D50 of the silicon negative electrode material is 3 to 7 μm, and / or the specific surface area of ​​the silicon negative electrode material is 1 to 8 m 2 / g.

7. The silicon negative electrode material according to claim 1, characterized in that: The silicon negative electrode material is prepared by the following steps: S1. preparing a polymer solution by using the polymer and an organic solvent; S2. Applying the polymer solution to the surface of the silicon material, and drying the polymer solution on the surface of the silicon material to form the coating layer on the surface of the silicon material.

8. The silicon negative electrode material according to claim 7, characterized in that: In S1, the polymer is prepared by the following steps: mixing the monomer used to prepare the polymer with an organic solvent and an initiator and reacting the mixture under an inert protective gas at 50 to 100° C. for 3 to 12 hours to obtain the polymer.

9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating disposed on the surface of the negative electrode current collector, wherein the negative electrode active coating contains the silicon negative electrode material according to any one of claims 1 to 8.

10. A lithium battery, characterized in that: The lithium battery comprises the negative electrode sheet as claimed in claim 9.